Point source SO2 dispersion modeling under various stack heights and meteorological conditions - Mohd. Yusoff, Mohd. Rashid; K., Sathiasilan; Mat, Ramli (1997)
This paper presents the results of the SO2 dispersion modeling from an oil fired power plant. The Industrial Source Complex (ISC) air dispersion model was used in the study. The ISC requires input on the source emission, physical stack parameters, and meteorological data. Results on the predicted maximum ground level SO2 concentration and the distance where it occurs under various stack heights (i.e 20 to 150 m) and seasonal meteorological conditions for a given oil fired power plant which consumes 1000 tons/day of fuel containing 3% sulfur were studied using the model.